THE MANAGEMENT OF MEDICAL REPORT COMPLETENESS FOR THE LEGALITY OF MEDICAL RECORD DOCUMENTS AT RSUD KRMT WONGSONEGORO (RSWN) SEMARANG CITY - Suyoko suyoko; Aylin Ivana; Arinda Juwita; Retno Astuti Setijaningsih (Dian Nuswantoro Semarang, 2021)
ABSTRACTBackground: Quality hospital services is reflected in the achieving of medical records. Improper medical record documentation would negatively affect the quality of service delivered to patients and it would disadvantage the hospital when medical disputes occur.Objective:Analyzing the management of medical record completeness at RSWN to guarantee the legality of medical record documents and its effect in supporting the completeness of medical record documents.Method:In this qualitative research, observation and interviews were conducted to 60 PJRM officers in the Arimbi ward, Banowati, Nakula I and Prabukresna. The obtained data were qualitatively and quantitatively analyzed based on several underlying theories.Results:The results showed that the completeness of some aspects includinghuman, money, method, material and machine elements was proper. The quantitative analysis showed 100%, while the qualitative analysis showed a percentage of 100% with the exception on the informed consent component with the potential for loss of 99%.Conclusions:The human element required periodic outreach to PPA. In the machine element, special computerswere needed for PJRM officers, and the importance of informed consent for patients undergoing hemodialysis to obtain medical records with strong legal force. Key Words :Management, Medical Record Completeness, Legality of Medical Records.